Transition flight modeling and robust control of a VTOL unmanned quad tilt-rotor aerial vehicle - Navya Thirumaleshwar Hegde; V.I. George; C Gurudas Nayak; Kamlesh Kumar (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
The development of fully autonomous Unmanned Aerial Vehicles (UAV) plays a major contribution towards reducing the risk to human life in various applications including rescue teams, border patrol, police and inspection of buildings, pipelines, coasts, and terrains. Tiltrotor hybrid UAV exhibit special application value due to its unique rotor structure. The variation in the model dynamics and aerodynamics due to the tilting rotors are the major key issues and challenges which attracted the attention of many researchers. This vehicle combines the hovering capabilities of a helicopter along with the high-speed cruise capabilities of a conventional airplane by tilting its four rotors. In the present research work, the authors attempt to model a quad tilt rotor UAV using Newton-Euler formulation. A dynamic model of the vehicle is derived mathematically for horizontal, vertical and transition flight modes. A robust H-infinity control strategy is proposed, evaluated and analyzed through simulation to control the flight dynamics of the different modes of the UAV. Simulation results shows that the tiltrotor UAV achieves transition successfully.